Límites y posibilidades en el proceso de virtualización tecno-pedagógica de universidades peruanas / Limits and possibilities in the techno-pedagogical virtualization process of Peruvian universities - Silvia Lavandera-Ponce; Lourdes Pérez-Sánchez; Ana María Martín-Cuadrado; Begoña Mora-Jaureguialde (Revista Latinoamericana de Tecnología Educativa, 2023)
The UTEC-UNED-TECSUP University Consortium took part in the eighth edition of the Support programme for the design and implementation of strategies for continuity of the Higher Education service in public universities of the Peruvian Ministry of Education (PMESUT), devised to promote the continuity of non-classroom-based educational service in public universities. This article presents the assessment carried out in four universities, with the aim of ensuring the ongoing digitization of education in the aftermath of the pandemic. Once the diagnosis had been made, the techno-pedagogical virtualization of 138 model courses was carried out in three phases: planning; curriculum design and teaching support; and implementation of the courses in the virtual classroom. Limitations were related to existing digital divides: time constraints, personal self-regulation and limited training in pedagogical and digital competences of teachers. Individualised support and tutoring measures were sought, increasing the number of synchronous sessions to facilitate assessment. The feedback focused on information, interaction and accountability on what has been done and the improvement of the didactic act in virtual mode. In conclusion, the complexity of the process was notable, as well as the high level of demand to achieve results which, although positive, encountered several obstacles arising from the different agents and elements involved.